Damascene 'Trench Art': a note on the manufacture of Mamluk Revival metalwork in early 20th-century Syria. (November 2014) - Milwright, Marcus; Baboula, Evanthia
<x content-type="archive" xml:space="preserve">Abstract</x> This article presents a detailed analysis of an inlaid brass pyxis produced in Damascus in the second decade of the 20th century. The object is made from the lower sections of two artillery shell casings, one of which carries markings of the German munitions factory where it was originally manufactured. This unusual object is contextualized within the larger phenomena of the 'Mamluk Revival' style in Europe and the Islamic world and of the 'Trench Art' made during and after World War I.